A high-peeling conductive polyacrylate pressure-sensitive adhesive and preparation method thereof
By optimizing the formulation and polymerization process, combined with dendritic silver-clad copper powder, high-peel conductive polyacrylate pressure-sensitive adhesive is prepared, which solves the problems of low peel strength and high cost of voltage-conducting adhesive, and achieves the improvement of conductive performance and stability .
Patent Information
- Application Number
- CN202210980749.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-08-16
- Publication Date
- 2025-02-07
- Estimated Expiration
- 2042-08-16
AI Technical Summary
While improving the conductivity, the existing voltage-conducting adhesives have reduced peeling strength and bonding strength, and are costly, which has problems such as unstable performance and poor heat resistance.
By optimizing the formulation and polymerization process, using segmented polymerization, combining the design system good solvent and non-good solvents, polyacrylate resins with high molecular weight and low glass transition temperature are prepared, and dendritic silver-clad copper powder is used as conductive filler. , reduce the amount of conductive material.
The high peel strength, good conductivity and stability of the voltage-conducting adhesive are achieved, while reducing costs and avoiding the problems of instability in performance and poor heat resistance.
Smart Images

Figure HDA0003800338020000011
Abstract
Description
Technical Field
[0001] The invention relates to the field of pressure-sensitive adhesives, in particular to a high-peeling conductive polyacrylate pressure-sensitive adhesive and a preparation method thereof. Background Art
[0002] At present, the electronics industry is developing rapidly, especially with the rapid rise of 5G electronic communications, the demand for electronic-related tapes, especially high-performance conductive pressure-sensitive adhesives, is increasing. However, in order to obtain better conductivity, conductive pressure-sensitive adhesives usually need to add a large amount of expensive conductive materials, such as spherical silver powder, copper powder, nano silver wire, etc., which not only increases the cost, but also the addition of a large amount of conductive fillers will deteriorate the performance of pressure-sensitive adhesives, resulting in a decrease in its peel strength and bonding strength. Pressure-sensitive adhesives have the disadvantages of unstable performance, poor heat resistance, and easy residual adhesive when peeling. Summary of the invention
[0003] The purpose of the present invention is to provide a high-peeling conductive polyacrylate pressure-sensitive adhesive and a preparation method thereof in view of the deficiencies in the prior art. The conductive pressure-sensitive adhesive has good conductivity and low cost. By combining the formulation and polymerization process optimization, adopting a segmented polymerization method, and adjusting the good solvent and non-good solvent of the design system, a polyacrylate resin with a high molecular weight and a low glass transition temperature can be obtained while ensuring that no gelation occurs during the polymerization process, thereby solving the problems of low peeling strength and residual adhesive of the conductive pressure-sensitive adhesive.
[0004] The purpose of the present invention is achieved through the following technical solutions:
[0005] A high-peeling conductive polyacrylate pressure-sensitive adhesive consists of the following components: 80-90 parts by weight of polyacrylate solution, 3-15 parts by weight of conductive filler, 0.2-1 parts by weight of coupling agent, 4.5-10 parts by weight of ethyl acetate and 0.5-2 parts by weight of crosslinking agent.
[0006] Furthermore, the polyacrylate solution is composed of the following components: 35-55 parts by weight of soft monomer, 8-20 parts by weight of hard monomer, 30-65 parts by weight of solvent, 0.22-0.44 parts by weight of initiator, 1.5-3.6 parts by weight of functional monomer and 3-15 parts by weight of rosin resin.
[0007] Furthermore, the hard monomer is one or more of methyl methacrylate, methyl acrylate, ethyl acrylate or vinyl acetate; the soft monomer is composed of butyl acrylate and isooctyl acrylate, and the mass ratio of butyl acrylate to isooctyl acrylate is 50:5-10:25; the functional monomer is composed of functional monomer A and functional monomer B, and the mass ratio of functional monomer A to functional monomer B is 1.4:0.1-3.5:0.1, the functional monomer A is acrylic acid or methacrylic acid, and the functional monomer B is hydroxyethyl acrylate or hydroxypropyl acrylate; the rosin resin is one or more of glycerol rosin ester, pentaerythritol rosin ester, and hydrogenated rosin glycerol ester.
[0008] Furthermore, the solvent is a mixed solvent of toluene and ethyl acetate, and the mass ratio of toluene to ethyl acetate in the mixed solvent is 1:1 to 3:1.
[0009] Furthermore, the initiator is azobisisobutyronitrile or benzoyl peroxide.
[0010] Furthermore, the polyacrylate solution is prepared by:
[0011] (1) 35 to 55 parts by weight of soft monomer, 0.10 to 0.24 parts by weight of initiator, 20 to 40 parts by weight of solvent and 1.5 to 3.6 parts by weight of functional monomer are mixed uniformly, transferred to a reaction bottle, and heated to 65 to 85° C. for reaction for 1 to 1.5 hours;
[0012] (2) then adding 5 to 15 parts by weight of solvent and 0.06 to 0.09 parts by weight of initiator, and continuing the reaction for 1 to 1.5 hours;
[0013] (3) Finally, 8 to 20 parts by weight of hard monomer, 0.06 to 0.11 parts by weight of initiator and 5 to 10 parts by weight of solvent are added, and the reaction is carried out for 1.5 to 2 hours. The temperature is then raised to 85° C., and the reaction is continued for 1 hour. Then, 3 to 15 parts by weight of hydrogenated rosin glycerol ester are added, and the temperature is lowered to room temperature to obtain a polyacrylic acid solution.
[0014] Furthermore, the conductive filler is a dendritic silver-coated copper powder, the particle size of the dendritic silver-coated copper powder is 5 to 20 μm, and the silver content is 5% to 30%.
[0015] Furthermore, the coupling agent is one of 3-(2,3-epoxypropoxy)propyltrimethoxysilane, γ-methacryloxypropyltrimethoxysilane and 3-mercaptopropyltrimethoxysilane.
[0016] Furthermore, the cross-linking agent is one of toluene diisocyanate, hexamethylene diisocyanate, and aluminum acetylacetonate.
[0017] The method for preparing the above-mentioned high-peeling conductive polyacrylate pressure-sensitive adhesive comprises the following steps:
[0018] (1) 3 to 15 parts by weight of a conductive filler, 0.1 to 1 parts by weight of a coupling agent, and 4.5 to 10 parts by weight of ethyl acetate are uniformly stirred at high speed, and then allowed to stand for 15 to 30 minutes to obtain a conductive filler solution;
[0019] (2) 80 to 90 parts by weight of a polyacrylate solution, 0.5 to 2 parts by weight of a cross-linking agent and the above-mentioned conductive filler solution are mixed and placed until the bubbles on the surface disappear, and then evenly coated on a film with a thickness of 5 to 50 μm, and the thickness of the dry glue is controlled to be 15 to 25 μm. Subsequently, the film is moved to 120 to 160° C. and dried for 5 to 15 minutes, and then placed in an oven at 60 to 90° C. and aged for 24 to 72 hours to obtain a high-peeling conductive polyacrylate pressure-sensitive adhesive.
[0020] Compared with the prior art, the present invention has the following advantages:
[0021] (1) The prepared conductive pressure-sensitive adhesive has high peel strength and no residual adhesive residue is left after peeling;
[0022] (2) The prepared conductive pressure-sensitive adhesive has good conductivity, high stability and good adhesion;
[0023] (3) The prepared conductive pressure-sensitive adhesive has low cost and excellent performance.
[0024] (4) Dendritic silver-coated copper powder is used. On the one hand, the bridging of the dendritic powder is conducive to the formation of a conductive path, which reduces the amount of conductive filler, improves the conductivity, and maintains the peel strength of the pressure-sensitive adhesive. On the other hand, by using the silver-coated copper method and taking copper as the matrix, the conductivity of silver is fully utilized, which greatly reduces the cost while maintaining the conductivity of the pressure-sensitive adhesive. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 Example 1 SEM image of high release conductive polyacrylate pressure-sensitive adhesive. DETAILED DESCRIPTION
[0026] In order to further understand the present invention, preferred embodiments of the present invention are described below in conjunction with examples. However, it should be understood that these descriptions are only for further illustrating the features and advantages of the present invention, rather than limiting the claims of the present invention.
[0027] The reagents or instruments used in the present invention without indicating the manufacturer are all conventional products that can be purchased from the market.
[0028] Example 1
[0029] (1) 25 parts by mass of butyl acrylate, 15 parts by mass of isooctyl acrylate, 0.15 parts by mass of azobisisobutyronitrile, 15 parts by mass of toluene, 10 parts by mass of ethyl acetate, 3 parts by mass of acrylic acid and 0.18 parts by mass of hydroxyethyl acrylate were mixed uniformly, and then transferred to a four-necked reaction bottle equipped with a thermometer and a stirring paddle. After nitrogen replacement for 0.5 h, the stirring was controlled at 250 r / min, and the temperature was raised to 75° C. for reaction for 1.5 h;
[0030] (2) adding 5 parts by mass of toluene, 3 parts by mass of ethyl acetate and 0.06 parts by mass of azobisisobutyronitrile, and continuing the reaction for 1.5 hours;
[0031] (3) Then, 11.5 parts by weight of vinyl acetate, 0.11 parts by weight of azobisisobutyronitrile, 2.5 parts by weight of toluene and 2.5 parts by weight of ethyl acetate were mixed evenly, added to the above four-necked reaction flask, reacted for 1.5 hours, then heated to 85° C., continued to react for 1 hour, added 12 parts by weight of hydrogenated rosin glycerol ester, stirred to dissolve, and cooled to room temperature to obtain a polyacrylate solution;
[0032] (4) 12 parts by weight of dendritic silver-coated copper powder with a particle size of 20 μm (silver content of 25%), 0.5 parts by weight of 3-(2,3-epoxypropoxy)propyltrimethoxysilane and 8 parts by weight of ethyl acetate were stirred at high speed and placed for 30 minutes to obtain a conductive filler solution; then 85 parts by weight of polyacrylate solution were added with the above conductive filler solution and 1.5 parts by weight of toluene diisocyanate, mixed evenly and placed in a 40°C vacuum oven until the bubbles on the surface disappeared, and then an automatic coating machine was used to evenly coat it on a 25 μm thick PET film, and the dry glue thickness was controlled to be 25 μm, and then moved to 160°C for drying for 5 minutes, and then placed in an oven at 60°C for aging for 48 hours to obtain a high-peeling conductive polyacrylate pressure-sensitive adhesive.
[0033] Figure 1 This is a SEM picture of the high release conductive polyacrylate pressure-sensitive adhesive prepared in Example 1. It can be seen that the surface of the high release conductive polyacrylate pressure-sensitive adhesive is relatively flat, wherein the dendritic conductive filler is well dispersed in the polyacrylate and is tightly combined with the polyacrylate resin.
[0034] Example 2
[0035] (1) 10 parts by mass of butyl acrylate, 25 parts by mass of isooctyl acrylate, 0.10 parts by mass of azobisisobutyronitrile, 15 parts by mass of toluene, 5 parts by mass of ethyl acetate, 1.4 parts by mass of acrylic acid and 0.1 parts by mass of hydroxyethyl acrylate were mixed uniformly, and then transferred to a four-necked reaction bottle equipped with a thermometer and a stirring paddle. After nitrogen replacement for 0.5 h, the stirring was controlled at 250 r / min, and the temperature was raised to 65° C. for reaction for 1 h;
[0036] (2) adding 2.5 parts by mass of toluene, 2.5 parts by mass of ethyl acetate and 0.06 parts by mass of azobisisobutyronitrile, and continuing the reaction for 1 hour;
[0037] (3) 8 parts by weight of methyl methacrylate, 0.06 parts by weight of azobisisobutyronitrile, 4 parts by weight of toluene and 2 parts by weight of ethyl acetate were mixed evenly and added to the four-necked reaction bottle to react for 1.5 hours. The mixture was then heated to 85° C. and continued to react for 1 hour. 3 parts by weight of glycerol rosin ester was added, stirred to dissolve, and then cooled to room temperature to obtain a polyacrylate solution.
[0038] (4) 15 parts by weight of dendritic silver-coated copper powder with a particle size of 5 μm (silver content of 12%), 0.8 parts by weight of γ-methacryloxypropyltrimethoxysilane and 10 parts by weight of ethyl acetate were stirred at high speed and allowed to stand for 15 minutes to obtain a conductive filler solution; then 80 parts by weight of polyacrylate solution were added with the above conductive filler solution and 0.5 parts by weight of hexamethylene diisocyanate, mixed evenly and placed in a 40°C vacuum oven until the bubbles on the surface disappeared, and then an automatic coating machine was used to evenly coat it on a PET film with a thickness of 5 μm, controlling the thickness of the dry glue to be 15 μm, and then moved to 120°C for drying for 15 minutes, and then placed in an oven at 90°C for aging for 24 hours to obtain a high-peeling conductive polyacrylate pressure-sensitive adhesive.
[0039] Example 3
[0040] (1) 50 parts by mass of butyl acrylate, 5 parts by mass of isooctyl acrylate, 0.24 parts by mass of benzoyl peroxide, 30 parts by mass of toluene, 10 parts by mass of ethyl acetate, 3.5 parts by mass of methacrylic acid and 0.1 parts by mass of hydroxyethyl acrylate were mixed uniformly, and then transferred to a four-necked reaction bottle equipped with a thermometer and a stirring paddle. After nitrogen replacement for 0.5 h, the stirring was controlled at 250 r / min, and the temperature was raised to 85° C. for reaction for 1.5 h;
[0041] (2) adding 10 parts by mass of toluene, 5 parts by mass of ethyl acetate and 0.09 parts by mass of benzoyl peroxide, and continuing the reaction for 1.5 hours;
[0042] (3) 20 parts by weight of methyl acrylate, 0.11 parts by weight of benzoyl peroxide, 5 parts by weight of toluene and 5 parts by weight of ethyl acetate were then mixed evenly and added to the four-necked reaction bottle to react for 2 hours. The mixture was then heated to 85° C. and reacted for 1 hour. 15 parts by weight of pentaerythritol rosin ester was added, stirred to dissolve, and then cooled to room temperature to obtain a polyacrylate solution.
[0043] (4) 3 parts by mass of dendritic silver-coated copper powder with a particle size of 20 μm (silver content of 18%), 0.1 parts by mass of 3-mercaptopropyltrimethoxysilane and 4.5 parts by mass of ethyl acetate were stirred at high speed and placed for 15 minutes to obtain a conductive filler solution; then 80 parts by mass of polyacrylate solution were added with the above conductive filler solution and 2 parts by mass of toluene diisocyanate, mixed evenly and placed in a 40°C vacuum oven until the bubbles on the surface disappeared, and then an automatic coating machine was used to evenly coat it on a 50 μm thick PET film, and the dry glue thickness was controlled to be 25 μm, and then moved to 140°C for drying for 10 minutes, and then placed in an oven at 70°C for aging for 48 hours to obtain a high-peeling conductive polyacrylate pressure-sensitive adhesive.
[0044] Example 4
[0045] (1) 35 parts by mass of butyl acrylate, 10 parts by mass of isooctyl acrylate, 0.18 parts by mass of azobisisobutyronitrile, 20 parts by mass of toluene, 10 parts by mass of ethyl acetate, 2.0 parts by mass of acrylic acid and 0.15 parts by mass of hydroxyethyl acrylate were mixed uniformly, and then transferred to a four-necked reaction bottle equipped with a thermometer and a stirring paddle. After nitrogen replacement for 0.5 h, the stirring was controlled at 250 r / min, and the temperature was raised to 80° C. for reaction for 1.5 h;
[0046] (2) adding 8 parts by mass of toluene, 4 parts by mass of ethyl acetate and 0.09 parts by mass of azobisisobutyronitrile, and continuing the reaction for 1.5 hours;
[0047] (3) 15 parts by weight of ethyl acrylate, 0.09 parts by weight of azobisisobutyronitrile, 6 parts by weight of toluene and 2 parts by weight of ethyl acetate were then mixed evenly and added to the four-necked reaction flask to react for 2 hours. The mixture was then heated to 85° C. and reacted for 1 hour. 10 parts by weight of pentaerythritol rosin ester was added, stirred to dissolve, and then cooled to room temperature to obtain a polyacrylate solution.
[0048] (4) 10 parts by mass of dendritic silver-coated copper powder with a particle size of 15 μm (silver content of 5%), 0.4 parts by mass of 3-mercaptopropyltrimethoxysilane and 9 parts by mass of ethyl acetate were taken and stirred at high speed, and then placed for 25 minutes to obtain a conductive filler solution; then 90 parts by mass of polyacrylate solution were added with the above conductive filler solution and 1.5 parts by mass of aluminum acetylacetonate, and the mixture was mixed evenly and placed in a vacuum oven at 40°C until the bubbles on the surface disappeared, and then the mixture was evenly coated on a PET film with a thickness of 50 μm using an automatic coating machine, and the thickness of the dry glue was controlled to be 20 μm, and then the mixture was moved to 140°C for drying for 10 minutes, and then placed in an oven at 90°C for aging for 24 hours to obtain a high-peeling conductive polyacrylate pressure-sensitive adhesive.
[0049] Example 5
[0050] (1) 30 parts by mass of butyl acrylate, 15 parts by mass of isooctyl acrylate, 0.18 parts by mass of azobisisobutyronitrile, 15 parts by mass of toluene, 15 parts by mass of ethyl acetate, 2.4 parts by mass of acrylic acid and 0.2 parts by mass of hydroxypropyl acrylate were mixed uniformly, and then transferred to a four-necked reaction bottle equipped with a thermometer and a stirring paddle. After nitrogen replacement for 0.5 h, the stirring was controlled at 250 r / min, and the temperature was raised to 75° C. for reaction for 1 h;
[0051] (2) adding 7 parts by mass of toluene, 3 parts by mass of ethyl acetate and 0.08 parts by mass of azobisisobutyronitrile, and continuing the reaction for 1.5 hours;
[0052] (3) Then, 12 parts by weight of methyl methacrylate, 0.09 parts by weight of azobisisobutyronitrile, 4 parts by weight of toluene and 2 parts by weight of ethyl acetate were mixed evenly, added to the above four-necked reaction bottle, reacted for 2 hours, then heated to 85° C., continued to react for 1 hour, added 10 parts by weight of hydrogenated rosin glycerol ester, stirred to dissolve, and cooled to room temperature to obtain a polyacrylate solution;
[0053] (4) 12 parts by weight of dendritic silver-coated copper powder with a particle size of 18 μm (silver content of 22%), 0.3 parts by weight of 3-(2,3-epoxypropoxy)propyltrimethoxysilane and 6 parts by weight of ethyl acetate were stirred at high speed and placed for 20 minutes to obtain a conductive filler solution; then 90 parts by weight of polyacrylate solution were added with the above conductive filler solution and 1.2 parts by weight of hexamethylene diisocyanate, mixed evenly and placed in a 40°C vacuum oven until the bubbles on the surface disappeared, and then an automatic coating machine was used to evenly coat it on a 25 μm thick PET film, and the dry glue thickness was controlled to be 20 μm, and then it was moved to 150°C for drying for 6 minutes, and then placed in an oven at 80°C for aging for 48 hours to obtain a high-peeling conductive polyacrylate pressure-sensitive adhesive.
[0054] Example 6
[0055] (1) 30 parts by mass of butyl acrylate, 12 parts by mass of isooctyl acrylate, 0.18 parts by mass of benzoyl peroxide, 16 parts by mass of toluene, 8 parts by mass of ethyl acetate, 2.4 parts by mass of acrylic acid and 0.1 parts by mass of hydroxyethyl acrylate were mixed uniformly, and then transferred to a four-necked reaction bottle equipped with a thermometer and a stirring paddle. After nitrogen replacement for 0.5 h, the stirring was controlled at 250 r / min, and the temperature was raised to 80° C. for reaction for 1.5 h;
[0056] (2) adding 8 parts by mass of toluene, 4 parts by mass of ethyl acetate and 0.09 parts by mass of benzoyl peroxide, and continuing the reaction for 1 hour;
[0057] (3) Then, 16 parts by weight of vinyl acetate, 0.1 parts by weight of benzoyl peroxide, 6 parts by weight of toluene and 3 parts by weight of ethyl acetate were mixed evenly, added to the above four-necked reaction bottle, reacted for 2 hours, then heated to 85° C., continued to react for 1 hour, added 15 parts by weight of hydrogenated rosin glycerol ester, stirred to dissolve, and cooled to room temperature to obtain a polyacrylate solution;
[0058] (4) 8 parts by mass of dendritic silver-coated copper powder with a particle size of 20 μm (silver content of 16%), 0.4 parts by mass of γ-methacryloxypropyltrimethoxysilane and 10 parts by mass of ethyl acetate were stirred at high speed and allowed to stand for 20 minutes to obtain a conductive filler solution; then 85 parts by mass of polyacrylate solution were added with the above conductive filler solution and 1.6 parts by mass of aluminum acetylacetonate, the mixture was mixed evenly and placed in a vacuum oven at 40°C until the bubbles on the surface disappeared, and then the mixture was evenly coated on a PET film with a thickness of 20 μm using an automatic coating machine, the thickness of the dry glue was controlled to be 20 μm, and then the mixture was moved to 120°C for drying for 15 minutes, and then placed in an oven at 60°C for aging for 72 hours to obtain a high-peeling conductive polyacrylate pressure-sensitive adhesive.
[0059] Comparative Example 1
[0060] (1) 25 parts by mass of butyl acrylate, 15 parts by mass of isooctyl acrylate, 0.15 parts by mass of azobisisobutyronitrile, 15 parts by mass of toluene, 10 parts by mass of ethyl acetate, 3 parts by mass of acrylic acid and 0.18 parts by mass of hydroxyethyl acrylate were mixed uniformly, and then transferred to a four-necked reaction bottle equipped with a thermometer and a stirring paddle. After nitrogen replacement for 0.5 h, the stirring was controlled at 250 r / min, and the temperature was raised to 75° C. for reaction for 1.5 h;
[0061] (2) adding 5 parts by mass of toluene, 3 parts by mass of ethyl acetate and 0.06 parts by mass of azobisisobutyronitrile, and continuing the reaction for 1.5 hours;
[0062] (3) Then, 11.5 parts by weight of vinyl acetate, 0.11 parts by weight of azobisisobutyronitrile, 2.5 parts by weight of toluene and 2.5 parts by weight of ethyl acetate were mixed evenly, added to the above four-necked reaction flask, reacted for 1.5 hours, then heated to 85° C., continued to react for 1 hour, added 12 parts by weight of hydrogenated rosin glycerol ester, stirred to dissolve, and cooled to room temperature to obtain a polyacrylate solution;
[0063] (4) 12 parts by mass of spherical silver-coated copper powder with a particle size of 20 μm (silver content of 25%), 0.5 parts by mass of 3-(2,3-epoxypropoxy)propyltrimethoxysilane and 8 parts by mass of ethyl acetate were taken and stirred at high speed, and then placed for 30 minutes to obtain a conductive filler solution; then 85 parts by mass of polyacrylate solution were added with the above conductive filler solution and 1.5 parts by mass of toluene diisocyanate, and the mixture was mixed evenly and placed in a vacuum oven at 40°C until the bubbles on the surface disappeared, and then the mixture was evenly coated on a PET film with a thickness of 25 μm using an automatic coating machine, and the dry glue thickness was controlled to be 25 μm, and then the mixture was moved to 160°C for drying for 5 minutes, and then placed in an oven at 60°C for aging for 48 hours to obtain a high-peeling conductive polyacrylate pressure-sensitive adhesive.
[0064] Comparative Example 2
[0065] (1) 25 parts by mass of butyl acrylate, 15 parts by mass of isooctyl acrylate, 0.15 parts by mass of azobisisobutyronitrile, 15 parts by mass of toluene, 10 parts by mass of ethyl acetate, 3 parts by mass of acrylic acid and 0.18 parts by mass of hydroxyethyl acrylate were mixed uniformly, and then transferred to a four-necked reaction bottle equipped with a thermometer and a stirring paddle. After nitrogen replacement for 0.5 h, the stirring was controlled at 250 r / min, and the temperature was raised to 75° C. for reaction for 1.5 h;
[0066] (2) adding 5 parts by mass of toluene, 3 parts by mass of ethyl acetate and 0.06 parts by mass of azobisisobutyronitrile, and continuing the reaction for 1.5 hours;
[0067] (3) Then, 11.5 parts by weight of vinyl acetate, 0.11 parts by weight of azobisisobutyronitrile, 2.5 parts by weight of toluene and 2.5 parts by weight of ethyl acetate were mixed evenly, added to the above four-necked reaction flask, reacted for 1.5 hours, then heated to 85° C., continued to react for 1 hour, added 12 parts by weight of hydrogenated rosin glycerol ester, stirred to dissolve, and cooled to room temperature to obtain a polyacrylate solution;
[0068] (4) 12 parts by mass of dendritic copper powder with a particle size of 20 μm, 0.5 parts by mass of 3-(2,3-epoxypropoxy)propyltrimethoxysilane and 8 parts by mass of ethyl acetate were taken and stirred at high speed, and then placed for 30 minutes to obtain a conductive filler solution; then 85 parts by mass of polyacrylate solution were added with the above conductive filler solution and 1.5 parts by mass of toluene diisocyanate, and the mixture was placed in a vacuum oven at 40°C until the bubbles on the surface disappeared, and then the mixture was evenly coated on a PET film with a thickness of 25 μm using an automatic coating machine, and the dry glue thickness was controlled to be 25 μm, and then the mixture was moved to 160°C for drying for 5 minutes, and then placed in an oven at 60°C for aging for 48 hours to obtain a high-peeling conductive polyacrylate pressure-sensitive adhesive.
[0069] Comparative Example 3
[0070] (1) 25 parts by mass of butyl acrylate, 15 parts by mass of isooctyl acrylate, 11.5 parts by mass of vinyl acetate, 0.32 parts by mass of azobisisobutyronitrile, 22.5 parts by mass of toluene, 15.5 parts by mass of ethyl acetate, 3 parts by mass of acrylic acid and 0.18 parts by mass of hydroxyethyl acrylate were mixed uniformly, and then transferred to a four-necked reaction bottle equipped with a thermometer and a stirring paddle, and replaced with nitrogen for 0.5 h, and then stirred at 250 r / min, and the temperature was raised to 75° C. for reaction for 4.5 h, and then raised to 85° C. for further reaction for 1 h, and then 12 parts by mass of hydrogenated rosin glycerol ester were added, stirred to dissolve, and then cooled to room temperature to obtain a polyacrylate solution;
[0071] (2) 12 parts by weight of dendritic silver-coated copper powder with a particle size of 20 μm (silver content of 25%), 0.5 parts by weight of 3-(2,3-epoxypropoxy)propyltrimethoxysilane and 8 parts by weight of ethyl acetate were stirred at high speed and placed for 30 minutes to obtain a conductive filler solution; then 85 parts by weight of polyacrylate solution were added with the above conductive filler solution and 1.5 parts by weight of toluene diisocyanate, mixed evenly and placed in a 40°C vacuum oven until the bubbles on the surface disappeared, and then an automatic coating machine was used to evenly coat it on a 25 μm thick PET film, and the dry glue thickness was controlled to be 25 μm, and then moved to 160°C for drying for 5 minutes, and then placed in an oven at 60°C for aging for 48 hours to obtain a high-peeling conductive polyacrylate pressure-sensitive adhesive.
[0072] The high release conductive polyacrylate pressure-sensitive adhesives prepared in Examples 1-6 and Comparative Examples 1-3 were subjected to the following tests. The test results are shown in Table 1.
[0073] 1. Peel strength test: Determine with reference to GB / T2792-1998 (180° peel strength test method for pressed adhesive tape). Select SUS304 stainless steel plate with specially treated surface as the adherend.
[0074] Adhesive: SUS304 stainless steel plate;
[0075] Tape test piece: cut into specifications of 25mm width and 180mm length;
[0076] Lamination conditions: stick the tape to the stainless steel plate in an environment of 23℃ / 65%RH, use a 2KG rubber roller to press back and forth 3 times without applying pressure, and leave it for 20 minutes;
[0077] Peeling speed: 180° peeling at a speed of 300 mm / min.
[0078] 2. Initial adhesion test: The initial adhesion performance test method of the tape is the rolling ball initial adhesion method (J.DOW method), which is determined in accordance with GB / T4852-2002 (pressure-sensitive adhesive tape initial adhesion test method). The test result is expressed by the ball number of the largest steel ball that the pressure-sensitive tape can adhere to.
[0079] Tape test piece: 20mm wide, 120mm long;
[0080] Test environment: carried out in a laboratory at 23℃ / 65%RH;
[0081] Sliding distance: 100mm;
[0082] Sliding distance: 100mm.
[0083] Conductivity test:
[0084] Place the sample flat on the test bench of the four-probe tester, bring the four-probe probe into close contact with the sample surface, and read the conductivity of the conductive glue from the computer after the current stabilizes.
[0085] Table 1
[0086] Glue thickness / μm Peel force / gf Initial adhesion / # <![CDATA[Conductivity / (S cm -1 )]]> Example 1 25 1811 17 <![CDATA[3.4*10 -2 ]]> Example 2 15 1377 12 <![CDATA[7.8*10 -2 ]]> Example 3 25 1921 18 <![CDATA[6.6*10 -5 ]]> Example 4 20 1702 16 <![CDATA[5.3*10 -3 ]]> Example 5 20 1575 13 <![CDATA[2.2*10 -2 ]]> Example 6 20 1757 16 <![CDATA[7.8*10 -3 ]]> Comparative Example 1 25 1768 17 <![CDATA[8.2*10 -4 ]]> Comparative Example 2 25 1677 17 <![CDATA[5.7*10 -4 ]]> Comparative Example 3 25 923 14 <![CDATA[4.9*10 -2 ]]>
[0087] From the performance tests of the examples and comparative examples in Table 1, it can be seen that in Examples 1-6, the conductive polyacrylate pressure-sensitive adhesives obtained have higher peel strength and good conductivity.
[0088] Compared with the embodiment, although comparative examples 1 and 2 also have good peel strength and initial adhesion, their conductivity is poor. Although comparative example 3 has good conductivity, its adhesive peel strength and initial adhesion are low. Therefore, the conductive polyacrylate pressure-sensitive adhesive obtained by the present invention has high peel strength and good conductivity, which solves the defect that common polyacrylate pressure-sensitive adhesives cannot take both peel strength and conductivity into account.
[0089] According to the disclosure of the above description, those skilled in the art to which the present invention belongs may also make appropriate changes and modifications to the above embodiments. Therefore, the present invention is not limited to the specific embodiments disclosed and described above, and some modifications and changes to the present invention should also fall within the scope of protection of the claims of the present invention. In addition, although some specific terms are used in this specification, these terms are only for the convenience of description and do not constitute any limitation to the present invention.
Claims
1. A high peeling conductive polyacrylate pressure-sensitive adhesive, characterized in that: The invention is composed of the following components: 80 to 90 parts by weight of polyacrylate solution, 3 to 15 parts by weight of conductive filler, 0.2 to 1 part by weight of coupling agent, 4.5 to 10 parts by weight of ethyl acetate and 0.5 to 2 parts by weight of crosslinking agent; The polyacrylate solution is composed of the following components: 35 to 55 parts by weight of soft monomer, 8 to 20 parts by weight of hard monomer, 30 to 65 parts by weight of solvent, 0.22 to 0.44 parts by weight of initiator, 1.5 to 3.6 parts by weight of functional monomer and 3 to 15 parts by weight of rosin resin; The hard monomer is one or more of methyl methacrylate, methyl acrylate, ethyl acrylate or vinyl acetate; The soft monomer is composed of butyl acrylate and isooctyl acrylate, and the mass ratio of butyl acrylate to isooctyl acrylate is 50:5 to 10:25; The functional monomer is composed of functional monomer A and functional monomer B, the mass ratio of functional monomer A to functional monomer B is 1.4:0.1 to 3.5:0.1, the functional monomer A is acrylic acid or methacrylic acid, and the functional monomer B is hydroxyethyl acrylate or hydroxypropyl acrylate; The rosin resin is one or more of glycerol rosin ester, pentaerythritol rosin ester, and hydrogenated rosin glycerol ester; The solvent is a mixed solvent of toluene and ethyl acetate, and the mass ratio of toluene to ethyl acetate in the mixed solvent is 1:1 to 3:1; The coupling agent is one or more of 3-(2,3-epoxypropoxy)propyltrimethoxysilane, γ-methacryloxypropyltrimethoxysilane and 3-mercaptopropyltrimethoxysilane; The conductive filler is a dendritic silver-coated copper powder, the particle size of the dendritic silver-coated copper powder is 5 to 20 μm, and the silver content is 5% to 30%; The high release conductive polyacrylate pressure-sensitive adhesive is prepared by the following steps: (1) 35-55 parts by weight of soft monomer, 0.10-0.24 parts by weight of initiator, 20-40 parts by weight of solvent and 1.5-3.6 parts by weight of functional monomer are mixed evenly, transferred to a reaction bottle, and heated to 65-85° C. for reaction for 1-1.5 hours; (2) then adding 5 to 15 parts by weight of solvent and 0.06 to 0.09 parts by weight of initiator, and continuing the reaction for 1 to 1.5 hours; (3) Finally, 8 to 20 parts by weight of hard monomer, 0.06 to 0.11 parts by weight of initiator and 5 to 10 parts by weight of solvent are added, and the mixture is reacted for 1.5 to 2 hours. The mixture is then heated to 85° C. and reacted for 1 hour. Then, 3 to 15 parts by weight of rosin resin are added, and the mixture is cooled to room temperature to obtain a polyacrylic acid solution. (4) 3 to 15 parts by weight of a conductive filler, 0.1 to 1 parts by weight of a coupling agent, and 4.5 to 10 parts by weight of ethyl acetate are uniformly stirred at high speed, and then allowed to stand for 15 to 30 minutes to obtain a conductive filler solution; (5) 80-90 parts by weight of polyacrylate solution, 0.5-2 parts by weight of cross-linking agent and the above conductive filler solution are mixed evenly and allowed to stand until the bubbles on the surface disappear, and then evenly coated on a film with a thickness of 5-50 μm, and the thickness of the dry adhesive is controlled to be 15-25 μm. The film is then moved to 120-160°C for drying for 5-15 minutes, and then placed in an oven at 60-90°C for aging for 24-72 hours to obtain a high-peeling conductive polyacrylate pressure-sensitive adhesive.
2. The high release conductive polyacrylate pressure-sensitive adhesive according to claim 1, characterized in that: The initiator is azobisisobutyronitrile or benzoyl peroxide.
3. The high release conductive polyacrylate pressure-sensitive adhesive according to claim 1, characterized in that: The cross-linking agent is one or more of toluene diisocyanate, hexamethylene diisocyanate, and aluminum acetylacetonate.
Citation Information
Patent Citations
Preparation method for pressure-sensitive adhesive
CN102559105A
Silver-coated copper powder, and conductive paste, conductive coating material and conductive sheet each of which uses same
CN106573303A
Cited By
Photoelectric visbreaking polyacrylate pressure-sensitive adhesive and preparation method thereof
CN120310473A